Impact of 18F-FDG PET/CT staging on management and prognostic stratification in head and neck squamous cell carcinoma: A prospective observational study. (August 2016) - Ryu, In Sun; Roh, Jong-Lyel; Kim, Jae Seung; Lee, Jeong Hyun; Cho, Kyung-Ja; Choi, Seung-Ho; Nam, Soon Yuhl; Kim, Sang Yoon
Abstract: Background: Accurate assessment of the extent of cancer is essential for appropriate treatment planning and outcome prediction. This study prospectively evaluated whether adding 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET)/computed tomography (CT) to the routine initial staging practice in head and neck squamous cell carcinoma (HNSCC) improved management and prognosis. Methods: All consecutive patients with newly diagnosed HNSCC who presented in October 2010 – December 2012 underwent conventional workups (CWU) followed by PET/CT. The clinical stage and management plans before and after PET/CT were compared. PET/CT was deemed to have no/low, moderate, and high impact on management planning depending on whether PET/CT changed the treatment modality or goal. The appropriateness of PET/CT staging and management impact was confirmed by histopathology and clinical follow-up, and its association with survival was analysed. Findings: Of the 248 patients, PET/CT changed the Tumour Node Metastasis (TNM) classification in 79 (31.9%). In the patients with discordant staging, PET/CT staging was significantly more sensitive and accurate than CWU staging (both P < 0.001). PET/CT had high or moderate impact on management in 39 (15.7%) patients. Patients with PET/CT upstaged disease had significantly worse progression-free survival (PFS) and overall survival (OS) than patients with no CWU-stage changes (3-year PFS = 56.8% versus 74.5%, P = 0.043; 3-year OS = 61.3% versus 85.3%, P = 0.006). Multivariate analyses revealed that PET/CT staging and second primary cancer were independent predictive factors for both PFS and OS ( P < 0.05, each). Interpretations: 18 F-FDG PET/CT added important staging information that improved management and prognostic stratification in HNSCC. Highlights: Positron emission tomography/computed tomography (PET/CT) staging changed the management plan in 39 (15.7%) of 248 patients with head and neck squamous cell carcinoma (HNSCC). It largely caused that PET/CT detected metastatic disease and second primary cancers better than conventional workups (CWU). PET/CT staging was significantly more predictive of survival outcomes than CWU staging. PET/CT added important staging information that improved management and prognostic stratification in HNSCC.